“FORENSIC-MEDICAL CHARACTERIZATION OF LESIONS OF THE HEAD STRUCTURE IN CHILDREN ASSOCIATED WITH THE EFFECTS OF BLUNT OBJECTS” - Sag‘dullayev , Narzulla Norkeldi o‘g‘li; Abdusalimov, Shavkat Kurbanmuratovich; Toshboyev, Ilxom Norbutayevich; Kurmasheva, Jamila Kamilovna (Educational Research in Universal Sciences, 2023)
An analysis of the expert opinions shows that when describing the elements of craniocerebral injuries, different terms are often used to name the same structures, sometimes not corresponding to generally accepted principles,recorded in the International Anatomical Nomenclature [31]. This complicates the production of additional and repeated examinations, analysis of localization injuries and mechanism of TBI formation.For this reason, we consider it possible to recall the main provisions of the anatomical structure of the CNS in order to unify forensic medical documentation.The brain is located in the cavity of the brain skull, includes a large (final) brain, diencephalon (thalamus, epithalamus, hypothalamus, III ventricle), midbrain (peduncles of the brain, aqueduct of the brain) and rhomboid brain,represented by the hindbrain and medulla oblongata. The hindbrain make up the bridge and cerebellum. The medulla oblongata, midbrain, and pons together form the brainstem. The large brain consists of two hemispheres - the right and left, which are connected to each other by a thick commissure (commissure) - the corpus callosum. Right and The left hemisphere is divided by a longitudinal fissure.